2011
DOI: 10.1016/j.virol.2010.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Mutational pathways and genetic barriers to CXCR4-mediated entry by human immunodeficiency virus type 1

Abstract: To examine mutational pathways that lead to CXCR4 use of HIV-1, we analyzed the genotypic and phenotypic characteristics of envelope sequences from a large panel of patient virus populations and individual clones containing different V3 mutations. Basic amino acid substitutions at position 11 were strong determinants of CXCR4-mediated entry, but required multiple compensatory mutations to overcome associated reductions in infectivity. In contrast, basic amino acid substitutions at position 25, or substitutions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…In particular, RMS showed that the V3 positions 5, 14, 19, 20, 21, 22, 24, 25 and 27 tightly interact with each other, thus forming a full interaction group significantly and strongly associated with CXCR4 usage. The presence of position 25 in this cluster is consistent with a recent study showing that basic amino acid substitutions at position 25 (R or K) alone are not sufficient to confer efficient CXCR4 usage [29]. Again, these results support that positions 11 and 25 alone are not sufficient to fully understand the mechanisms underlying different coreceptor usage, and highlight the association between multiple amino acid changes in V3 and efficient CXCR4 usage.…”
Section: Discussionsupporting
confidence: 90%
“…In particular, RMS showed that the V3 positions 5, 14, 19, 20, 21, 22, 24, 25 and 27 tightly interact with each other, thus forming a full interaction group significantly and strongly associated with CXCR4 usage. The presence of position 25 in this cluster is consistent with a recent study showing that basic amino acid substitutions at position 25 (R or K) alone are not sufficient to confer efficient CXCR4 usage [29]. Again, these results support that positions 11 and 25 alone are not sufficient to fully understand the mechanisms underlying different coreceptor usage, and highlight the association between multiple amino acid changes in V3 and efficient CXCR4 usage.…”
Section: Discussionsupporting
confidence: 90%
“…6A). Interestingly, none of the X4 sequences have positively charged amino acid R or K at V3 position 11 or 25, which are important for X4 usage in other HIV-1 subtypes (1921). This implies different evolutionary pathway of coreceptor switching in CRF01_AE HIV-1.…”
Section: Resultsmentioning
confidence: 99%
“…The genetic features of the X4 variants in CRF01_AE cluster 4 are also different from previously found in other HIV-1 subtypes. In particular, none of the X4 sequences in CRF01_AE cluster 4 have positively charged amino acid (R or K) at V3 positions 11 or 25, which are key amino acids for X4 usage observed in other subtypes (1921). Instead, all of them lost the V3 glycan (the N301 glycan), and nearly all have residue K at V3 position 7.…”
Section: Discussionmentioning
confidence: 99%
“…An accumulation of basic amino acid substitutions at specific positions in the V3 loop of SU is associated with the coreceptor switch, which is presumed to increase specificity or affinity for CXCR4 (Wilen et al 2011). There are other positions in Env but outside of V3 that also contribute to the X4 phenotype, but the specific contribution of these other sites is not clear (Hoffman et al 2002;Pastore et al 2006;Huang et al 2008Huang et al , 2011. There also seem to be differences among the subtypes for their propensity to evolve X4 variants, with X4 variants being more common in subtype D isolates (Tscherning et al 1998;Huang et al 2007).…”
Section: Target Cells T-cell Subsetsmentioning
confidence: 99%